The role of the estimated glomerular filtration rate and body roundness index in the risk assessment of uric acid-lowering therapy-resistant gout in U.S. adults: evidence from the National Health and Nutrition Examination Survey (2007–2018) - Mengyuan Zhu; Xingqiang Wang; Zining Peng; Weitian Yan; Qian Deng; Meihui Li; Nian Liu; Ling Zhang (Renal Failure)
Objective To explore the risk factors for uric acid-lowering therapy-resistant gout (UALT-RG) and its relationships with the estimated glomerular filtration rate (eGFR), body roundness index (BRI), and visceral adiposity index (VAI) via 2007–2018 National Health and Nutrition Examination Survey (NHANES) data.Methods We calculated the BRI using waist circumference and standing height; the VAI using triglycerides (TGs), high-density lipoprotein cholesterol (HDL-C), and body mass index (BMI); and the eGFR from serum creatinine levels. We also collected gout data. We explored the relationships of the eGFR, BRI, and VAI with UALT-RG risk via univariable and multivariable weighted logistic regression, trend analysis, and restricted cubic splines.Results Among the 1,811 patients with gout, ∼9.08% had UALT-RG; these patients were more likely to have obesity, comorbid diabetes (36% [27–47%] vs. 25% [22–28%]) or impaired kidney function (eGFR < 60 mL/min/1.73 m2, 34.5% [27–43%] vs. 22.5% [20–26%]); be former smokers; and take colchicine (10% [5.6–19%] vs. 4.3% [2.8–6.7%]). Logistic regression and trend analysis suggested that an elevated BRI and decreased eGFR were independent risk factors and potential screening indicators for UALT-RG. Restricted cubic spline analysis revealed a negative linear trend between the eGFR and UALT-RG risk (p-overall < 0.0001) and a significant positive correlation between the BRI and UALT-RG risk (p-overall < 0.0001).Conclusion An increased BRI and decreased eGFR may be independent risk factors and assessment indicators for UALT-RG in U.S. adults. It is necessary to monitor serum urate levels more closely and conduct early multidisciplinary comanagement when gout is comorbid with visceral obesity and chronic kidney disease stages 3–5.